From substituent effects to applications: enhancing the optical response of a four-component assembly for reporting ee values. Issue 7 (11th March 2016) - Lin, Chung-Yon; Giuliano, Michael W.; Ellis, Bryan D.; Miller, Scott J.; Anslyn, Eric V.
Abstract : Substituent effect studies were conducted on a dynamic chiral alcohol sensor, leading to a new sensor with lower errors. Abstract : High-throughput screening for asymmetric catalysts has stimulated an interest in optically-based enantiomeric-excess (ee) sensors, primarily for their improved time and cost efficiency when compared to the standard HPLC analysis. We present herein substituent-effect studies on a recently reported Zn(ii ) multicomponent assembly that is used for chiral, secondary alcohol ee determination. The systematic altering of assemblies formed from select substituted pyridyl ligands pointed to the conclusion that steric effects dominate the mode of interaction at the pyridyl 3- and 6-positions. From these results we identified a new Zn(ii )-centered multicomponent assembly with a higher dynamic range than previously reported. Calibration curves of the CD signals resulting from the new assembly led to an ee assay with a 1.7% error. To further the utility of the new assembly, a correlation was developed between alcohol substituent size to the respective enantiopure CD value.